Bradycardia-to-Delivery Interval and Fetal Outcomes in Umbilical Cord Prolapse. Issue 4 (22nd December 2021) - Wong, L.; Tse, W.T.; Lai, C.Y.; Hui, A.S.Y.; Chaemsaithong, P.; Sahota, D.S.; Poon, L.C.; Leung, T.Y.
Abstract : ( Acta Obstet Gynecol Scand . 2021;100:170–177) Umbilical cord prolapse is an emergency with risk for significant complications, including prematurity and birth asphyxia. As cord compression and umbilical arterial vasospasm can lead to fetal hypoxia and birth asphyxia, rapid delivery is required to prevent fetal brain injury, cerebral palsy and death. However, studies have found improved Apgar scores associated with longer decision-to-delivery intervals in some cases of umbilical cord prolapse. Bradycardia-to-delivery interval may be a better predictor of perinatal outcomes because cord prolapse and onset of fetal hypoxia may occur before the decision to deliver. This study aimed to investigate the relationship between bradycardia-to-delivery interval or decision-to-delivery interval and adverse neonatal outcomes, specifically focusing on the range of fetal heart rate abnormalities in cases of umbilical cord prolapse.